Non-catalytic synthesis of zinc oxide (ZnO) nanomaterials and their photoluminescence properties - Ladines, Alvin Noe C. (Animo Repository, 2008)
Zinc Oxide nanomaterials were synthesized on glass substrate through the non-catalytic horizontal vapor phase growth method. Nanobells with average width of 200 nm were grown when the growth temperature was set at 12000C and 10000C. Nanowires with mean diameter of 100 nm were dominant at growth temperatures of 8000C and 6000C. Shorter growth time resulted in the formation of needle-like structures which are 2 micrometers in length. Increasing the growth time corresponded to the growth of nanowires with average length of 10 micrometers. XRD measurements showed that the synthesized nanostructures have a hexagonal wurtzite structure with growth preference in the (001), (101) and (10 1) directions. The room temperature photoluminescence spectra showed an intense ultraviolet emission (UV) at 3.26 eV with weak emissions in the visible light regime. The strong UV emission can be attributed to the recombination of free excitons though an exciton-exciton collision process. Meanwhile, the deep level emissions are caused by oxygen vacancies in ZnO and the emission results in the recombination of the photogenarated hole with an electron occupying the oxygen vacancy. It is proposed that growth mechanism involved in the formation of ZnO nanostructures is the vapor-solid process because no catalyst was used.